2014
DOI: 10.5812/ircmj.7887
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan Fast in Patients With Coronary Artery Disease

Abstract: Background:Fasting during the month of Ramadan is of vital significance amongst Muslims; however, little is known about the effects of this kind of fasting on patients with coronary artery disease (CAD).Objectives:This nonrandomized prospective observational pilot study was designed to investigate the effects of Ramadan fast on the symptoms of CAD.Patients and Methods:Patients with documented CAD were consecutively (nonrandomized) included in the study, and those with heart failure (ejection fraction < 50%), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…More recently, Mousavi et al . [ 6 ] prospectively studied 148 patients with documented CAD and normal ejection fraction. They found that patients with CAD were able to observe Ramadan fast safely, and their symptoms were not significantly different from that of the nonfasting ones.…”
Section: Stable Cardiac Diseasementioning
confidence: 99%
“…More recently, Mousavi et al . [ 6 ] prospectively studied 148 patients with documented CAD and normal ejection fraction. They found that patients with CAD were able to observe Ramadan fast safely, and their symptoms were not significantly different from that of the nonfasting ones.…”
Section: Stable Cardiac Diseasementioning
confidence: 99%
“…Pekdemir et al identified significant association of the change of dietary and sleeping patterns during the month of Ramadan, with the change in health conditions of patients with cardiovascular diseases [ 14 ]. Contrary to this, Mousavi et al observed no significant change among patients with CAD during and after the month of Ramadan, since the number of patients that were admitted during the given period was like those in normal days [ 13 ]. For Chamsi-Pasha et al individuals exposed to the high-level risks of ACS are advised to exempt fasting to avoid severe illness [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alshareef observed a significant increase in the prevalence of cardiovascular diseases and ACS among different populations, specifically during and after Ramadan [ 12 ]. Mousav et al provided a detailed analysis regarding the effect of fasting on coronary artery disease (CAD) [ 13 ]. Findings indicated that patients with CAD were able to observe fast, while symptoms of chest pain were like that in normal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic and clinical effects of RF have been previously studied systematically [1]. Most of the studies suggested that RF is safe in stable patients with Coronary Artery Disease (CAD) [2,3].…”
Section: Introductionmentioning
confidence: 99%